A fast chiller power demand response control strategy for buildings connected to smart grid. (1st January 2015) - Xue, Xue; Wang, Shengwei; Yan, Chengchu; Cui, Borui
Highlights: A fast chiller power demand response control strategy for buildings is developed. Buildings could act as "operating reserves" to respond to the requests of smart grid rapidly. Significant power demand reduction is achieved without sacrificing comfort too much. Disordered chilled water control and uneven comfort degradation are effectively addressed. Buildings could receive grid incentives in both demand reduction and energy saving. Abstract: With the increasing integration of renewable energies into electrical grids, power imbalance has become one of the most critical issues in grid operations. The end-users at power demand side can actually make use of their demand reduction potentials to contribute to the grid power balance. Conventional demand responses of end-users can provide considerable power demand reductions, but the demand responses are usually subject to significant delay and cannot fulfill the needs of grid real time operation. In this paper, a fast chiller power demand response control strategy for commercial buildings is therefore proposed which facilitates buildings to act as grid "operating reserves" by providing rapid demand responses to grid request within minutes. However, simply shutting down some essential operating chillers would result in disordered chilled water flow distribution and uneven indoor thermal comfort degradation. This strategy has therefore taken essential measures to solve such problems effectively. Simulation case studies are conducted to investigate the operation dynamics and energy performance of HVAC systems in the demand response events controlled by the strategy. Results show that fast and significant power demand reductions can be achieved without sacrificing the thermal comfort too much.